Relación longitud-peso, coloración y ubicación en el ambiente de juveniles de Pinguipes chilensis en Bahía La Herradura, Coquimbo, Chile - Flores, Héctor; Araus, María Ignacia (Revista de Biología Marina y Oceanografía, 2018)
Pinguipes chilensis (Chilean sandperch) is an endemic species of the Southeast Pacific Ocean. Studies have generally included specimens of a total length (Lt) of more than 21 cm, there being no formal antecedents of specimens of a smaller Lt, weakness that motivates this study. It was determined for the Lt-Pt relation (Pt= 0.000005Lt3,1101, R2= 0.974) and Fulton’s average condition factor (0.81). Three ontogenetic color morphs are characterized, which are arranged in different environments and inhabit heterogeneous backgrounds, with sandy areas, others with abundant rocks and cracked rocks, which allow fish to take refuge